Empowerment Strategy of Ledre MSMEs through the Increasing of Stakeholder's Role - Purhayati, Purhayati; Karsidi, Ravik; Padmaningrum, Dwiningtyas (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the development of Ledre MSMEs, examine the role of stakeholders in the empowerment process, and identify empowerment strategies for Ledre entrepreneurs in Gapluk Village, Purwosari Sub-District, Bojonegoro Regency. Methodology/approach: This study employs a qualitative descriptive method. Data collection techniques included observation, semi-structured interviews, and documentation. Miles and Huberman’s interactive analysis model was used to explore the development of Ledre MSMEs in Gapluk Village and the role of stakeholders in community empowerment, as well as SWOT analysis to determine appropriate strategies for empowering Ledre MSMEs in Gapluk Village. Results/findings: The results showed that the number of Ledre MSMEs in Gapluk Village has declined from 2020 to 2024 due to various factors. Therefore, efforts to empower Ledre MSMEs to overcome this decline must involve stakeholders from the village to the regency-level government, relevant agencies or institutions, and Ledre business actors such as policymakers, coordinators, facilitators, implementers, and accelerators. Conclusions: Collaboration between stakeholders is expected to create the right strategy for empowering Ledre MSMEs in Gapuk Village according to the potential strengths and weaknesses, challenges, and development opportunities they face. Limitations: The limitations of this study include the geographical coverage limited to Ledre MSMEs in Gapluk Village as the case study location; therefore, the results may not be generalizable to other regions. Contribution: The results of this study can serve as a reference for policymakers in formulating policies that support the empowerment of MSMEs through collaboration between MSMEs actors, BUMDes, and related stakeholders to maximize local potential in community empowerment efforts.